Isoquercitrin, a flavonoid glucoside, exerts a positive effect on osteogenesis in vitro and in vivo. (5th January 2019) - Li, Jing; Wang, Xuxia; Wang, Yingzi; Lu, Chengyan; Zheng, Dehua; Zhang, Jun
Abstract: Isoquercitrin (quercetin-3-O-β-d -glucopyranoside) possess various pharmacological effect as a biologically active compound. The aim of the present study was to investigate its potential effects on the proliferation and osteoblastic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) in vitro and bone formation in the mid-palatal suture during rapid maxillary expansion (RME) in vivo. Cell proliferation of rat BMSCs was detected by cell-counting kit- 8 (CCK-8) assay. Alkaline phosphatase (ALP) activity assay and alizarin red staining were used to evaluate osteogenic differentiation of BMSCs. Furthermore, the expression levels of osteogenesis-related genes including runt-related transcription factor 2 (Runx2), bone sialoprotein (BSP) and activating transcription factor 6 (ATF6) were measured by real-time RT-PCR. In vivo, thirty-six male 6-week-old Wistar rats with or without suture expansion receive systemic administration of isoquercitrin or saline solution. Micro-CT, HE and Masson staining were used to compare the morphological changes between the groups. Bone morphogenetic protein 2 (BMP2) expression in the suture was detected using immunohistochemical staining. Our results showed that isoquercitrin significantly promoted cell proliferation, ALP activity and mineral deposition in the range from 0.01 to 1 μM. Moreover, the expression levels of Runx2, BSP and ATF6 were also upregulated. The measurement of micro-CT imaging and histological examinations demonstrated that daily oral administration of isoquercitrin (10 mg/kg) increased bone formation compared to the other groups. Furthermore, the expression level of BMP2 was also augmented in the presence of isoquercitrin. Consequently, those findings showed that isoquercitrin exerts stimulatory effects on osteogenesis in vitro and in vivo, suggesting that isoquercitrin could be a potential candidate for preventing relapse following RME within palatal sutures. Highlights: Isoquercitrin enhanced osteogenic differentiation of BMSCs. Isoquercitrin improved the gene expression of Runx2 and BSP. Oral administration of isoquercitrin stimulated bone formation during RME. Isoquercitrin upregulated the expression of BMP2 in the midpalatal suture.